2007
DOI: 10.1001/archsurg.142.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Depth of Portal Vein Wall Invasion After Curative Resection for Pancreatic Adenocarcinoma

Abstract: The depth of portal vein (PV) wall invasion is a prognostic factor for survival after curative pancreatic resection for pancreatic ductal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
76
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 45 publications
6
76
3
3
Order By: Relevance
“…Type 1-partial venous excision with direct closure; type 2-partial venous excision using a patch; type 3-segmental resection with primary veno-venous anastomosis; and type 4-segmental resection with interposed venous conduit and at least two anastomoses. Portal venous tumor invasion has been shown to be a negative prognostic factor [3], and the depth of tumor invasion is even more accurate for determining survival [26]. Deeper portal vein invasion into the tunica media or intima was an independent prognostic factor for poor survival.…”
Section: Venous Involvementmentioning
confidence: 99%
“…Type 1-partial venous excision with direct closure; type 2-partial venous excision using a patch; type 3-segmental resection with primary veno-venous anastomosis; and type 4-segmental resection with interposed venous conduit and at least two anastomoses. Portal venous tumor invasion has been shown to be a negative prognostic factor [3], and the depth of tumor invasion is even more accurate for determining survival [26]. Deeper portal vein invasion into the tunica media or intima was an independent prognostic factor for poor survival.…”
Section: Venous Involvementmentioning
confidence: 99%
“…Depth of venous involvement correlates with imaging characteristics and prognosis. Fukuda et al 3 showed that the depth of vein invasion significantly alters survival after curative resection. Deeper wall invasion into the tunica media or intima was associated with a poorer 1-year survival rate, similar to that of patients undergoing non-curative resection.…”
mentioning
confidence: 99%
“…With deeper portal vein wall invasion into the tunica media or intima, the survival is similar to those with non-curative surgery. The depth of portal vein invasion appears to correlate with preoperative CT portogram type C and D and a tumor diameter more than 45 mm [6].Although autologous venous and polytetrafluoroethylene grafts are conduits of choice for portal vein reconstruction, a generous Cattell-Braasch manoeuvre, wherein the ligament of Treitz is incised and hepatic flexure dissected liberally, serves to mobilise the root of mesentery and helps in moving it cranially. Mobilising the liver by incising the falciform, coronary and triangular ligaments causes a caudal displacement of the liver.…”
mentioning
confidence: 99%